2022
DOI: 10.1002/open.202200055
|View full text |Cite
|
Sign up to set email alerts
|

A Ratiometric Fluorescence Probe for Selective Detection of ex vivo Methylglyoxal in Diabetic Mice

Abstract: Accurate monitoring of methylglyoxal (MGO) at cell and living level was crucial to reveal its role in the pathogenesis of diabetes since MGO was closely related to diabetes. Herein, a ratiometric fluorescence strategy was constructed based on the capture probe 2,3‐diaminonaphthalene (DAN) for the specific detection of MGO. Compared to the fluorescent probes with a single emission wavelength, the ratiometric mode by monitoring two emissions can effectively avoid the interference from the biological background, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…MGO, produced during the glycolysis process in living systems, has a notable connection with diabetes and is regarded as an emerging biomarker for diabetes and its complications. , It has been revealed that the level of MGO exhibits over 3-fold increase in the serum of diabetic mice , and up to 10-fold increase in diabetic complication regions. In order to evaluate the sensing capability in real-world applications, we test 16 serum samples from healthy mice (H1–H8) and diabetic mice (D1–D8) by the photo-enhanced chemo-transistor (Figure a). In the dark, the chemo-transistors hardly distinguish the positive sample from the negative sample, yielding a difference in the Δ V Dirac response smaller than 3 mV (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…MGO, produced during the glycolysis process in living systems, has a notable connection with diabetes and is regarded as an emerging biomarker for diabetes and its complications. , It has been revealed that the level of MGO exhibits over 3-fold increase in the serum of diabetic mice , and up to 10-fold increase in diabetic complication regions. In order to evaluate the sensing capability in real-world applications, we test 16 serum samples from healthy mice (H1–H8) and diabetic mice (D1–D8) by the photo-enhanced chemo-transistor (Figure a). In the dark, the chemo-transistors hardly distinguish the positive sample from the negative sample, yielding a difference in the Δ V Dirac response smaller than 3 mV (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] As a highly active molecule, MGO can react with proteins, DNA, and lipids to form advanced glycation end products, resulting in irreversible cell structural damage and dysfunction, which is closely associated with pathologies of diverse human diseases including obesity, Alzheimer's disease, cardiovascular disease, and diabetes. [4][5][6][7][8][9][10] The detoxification method of MGO mainly relies on glyoxalase 1 and glyoxalase 2, which can convert MGO into non-toxic D-lactic acid to regulate the levels of MGO in cells. [11][12][13][14] Indeed, elevated levels of MGO have been observed in cancer cells due to the aerobic glycolysis pathway and are involved in tumor progression.…”
Section: Introductionmentioning
confidence: 99%